Legal Protection for Indonesian Migrant Workers Abroad During the Covid-19 Pandemic - Tribowo, Andita; Akbar Widya Pratama; Margaretha Evi Yuliana (Universitas Duta Bangsa Surakarta, 2022)
Law No. 13 of 2003 concerning Manpower states that every worker has the same rights and opportunities to choose, get, or change jobs both within and outside the country. Then Law No. 39 of 2004 concerning the Placement and Protection of Indonesian workers abroad and its implementing regulations. However, the facts on the ground show that there are still many cases that afflict Indonesian workers abroad who have not received complete and safe protection. In fact, many of them don't even know what protection they get. The problem in this research is how is the legal protection of Indonesian workers abroad during Covid 19. This research method uses a sociological juridical approach, with data collection from field studies and literature studies, to determine the legal protection of Indonesian workers abroad. The data obtained were analyzed qualitatively. Based on the results of the study found that Indonesian migrant workers abroad get legal protection. This protection can be seen from the regulations made by the government in providing protection for the rights of Indonesian migrant workers while carrying out their duties abroad. During the Covid 19 outbreak, the Indonesian government provided various assistance and attention to the affected Indonesian migrant workers. However, the protection of Indonesian migrant workers during Covid 29 from the Indonesian government still has weaknesses. Many Indonesian migrant workers feel that their rights have not been fulfilled during Covid 19. Even the delay in responding makes Indonesian migrant workers feel unnotified. So protection during Covid 19 itself cannot be carried out optimally. Keywords: Legal protection, Indonesian workers, overseas